2021
DOI: 10.1186/s40623-020-01288-x
|View full text |Cite
|
Sign up to set email alerts
|

International Geomagnetic Reference Field: the thirteenth generation

Abstract: In December 2019, the International Association of Geomagnetism and Aeronomy (IAGA) Division V Working Group (V-MOD) adopted the thirteenth generation of the International Geomagnetic Reference Field (IGRF). This IGRF updates the previous generation with a definitive main field model for epoch 2015.0, a main field model for epoch 2020.0, and a predictive linear secular variation for 2020.0 to 2025.0. This letter provides the equations defining the IGRF, the spherical harmonic coefficients for this thirteenth g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
314
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 501 publications
(385 citation statements)
references
References 44 publications
2
314
0
5
Order By: Relevance
“…The task force released IGRF-13 on 19 December 2019. The official set of spherical harmonic coefficients as well as a discussion of the general features of the IGRF-13 model can be found in Alken et al (2020b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The task force released IGRF-13 on 19 December 2019. The official set of spherical harmonic coefficients as well as a discussion of the general features of the IGRF-13 model can be found in Alken et al (2020b).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, in the past two decades, the northern polar region has experienced large variations with the location of the magnetic dip pole moving in an irregular manner (Chulliat et al 2010;Thébault et al. 2015;Alken et al 2020b;Livermore et al 2020). In the section Retrospective analysis of IGRF-12 secular variation models, we examine the performance of the IGRF-12 SV forecasts over the 2015-2020 time interval to investigate how physics-based approaches compare to the empirical SV derived from recent satellite data.…”
Section: Introductionmentioning
confidence: 99%
“…These values are given in Table 4. Figure 4 shows comparisons between the power spectra of each of our candidate models and the final IGRF-13 models (Alken et al 2020a). For the DGRF at 2015.0 we see excellent agreement in the spectra, with our candidate very close to the final chosen model of the median of all candidates (see Alken et al 2020b).…”
Section: Main Field At 20150mentioning
confidence: 68%
“…7a, b). The drifts of western minimum and saddle point most likely continue according to both the Mag.num and also the final IGRF-13 (Alken et al 2020b) predictions, as shown by the red squares and blue crosses, respectively. The drift of the eastern minimum has already slowed down in recent years, and the models predict that it will not drift further eastward in the next 5 years.…”
Section: At Earth's Surfacementioning
confidence: 78%